Prognostic value of global longitudinal layer specific strain for patients with heart failure with reduced ejection fraction. (25th November 2020) - Johnsen, C; Sengeloev, M; Joergensen, P; Bruun, N; Modin, D; Alhakak, A; Schou, M; Gislason, G; Fritz-Hansen, T; Shah, A; Biering-Soerensen, T
Abstract: Background: Novel echocardiographic software allows for layer-specific evaluation of myocardial deformation by 2-dimensional speckle tracking echocardiography. Endocardial, epicardial- and whole wall global longitudinal strain (GLS) may be superior to conventional echocardiographic parameters in predicting all-cause mortality in patients with heart failure with reduced ejection fraction (HFrEF). Purpose: The purpose of this study was to investigate the prognostic value of endocardial-, epicardial- and whole wall GLS in patients with HFrEF in relation to all-cause mortality. Methods: We included and analyzed transthoracic echocardiographic examinations from 1, 015 patients with HFrEF. The echocardiographic images were analyzed, and conventional and novel echocardiographic parameters were obtained. A p value in a 2-sided test <0.05 was considered statistically significant. Cox proportional hazards regression models were constructed, and both univariable and multivariable hazard ratios (HRs) were calculated. Results: During a median follow-up time of 40 months, 171 patients (16.8%) died. A lower endocardial (HR 1.17; 95% CI (1.11–1.23), per 1% decrease, p<0.001), epicardial (HR 1.20; 95% CI (1.13–1.27), per 1% decrease, p<0.001), and whole wall (HR 1.20; 95% CI (1.14–1.27), per 1% decrease, p<0.001) GLS were all associated with higher risk of death (Figure 1). Both endocardial (HR 1.12; 95% CI (1.01–1.23), p=0.027), epicardial (HR 1.13; 95% CI (1.01–1.26), p=0.040) and whole wall (HR 1.13; 95% CI (1.01–1.27), p=0.030) GLS remained independent predictors of mortality in the multivariable models after adjusting for significant clinical parameters (age, sex, total cholesterol, mean arterial pressure, heart rate, ischemic cardiomyopathy, percutaneous transluminal coronary angioplasty and diabetes) and conventional echocardiographic parameters (left ventricular (LV) ejection fraction, LV mass index, left atrial volume index, deceleration time, E/e', E-velocity, E/A ratio and tricuspid annular plane systolic excursion). No other echocardiographic parameters remained an independent predictors after adjusting. Furthermore, endocardial, epicardial and whole wall GLS had the highest C-statistics of all the echocardiographic parameters. Conclusion: Endocardial, epicardial and whole wall GLS are independent predictors of all-cause mortality in patients with HFrEF. Furthermore, endocardial, epicardial and whole wall GLS were superior prognosticators of all-cause mortality compared with all other echocardiographic parameters. Funding Acknowledgement: Type of funding source: Public hospital(s). Main funding source(s): Herlev and Gentofte Hospital